2020
DOI: 10.1177/1055665620944759
|View full text |Cite
|
Sign up to set email alerts
|

Change in Initial Tympanostomy Tube Placement Timing Yields Decreased Burden of Care Without Increased Complications in Patients With Cleft Lip and Palate

Abstract: Objective: To report a practice audit of the consequences of a change in protocol in the timing of placement of tympanostomy tubes in infants with cleft lip and palate. Participants: All children with a diagnosis of cleft lip and palate, treated between November 1998 and May 2006 under the old protocol, and between December 2012 and July 2016 under a new protocol. Under the old protocol, tympanostomy tubes were first inserted at the time of lip repair at around age 2 months. Under the new protocol, tympanostom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 20 publications
0
3
1
Order By: Relevance
“…Several studies on the timing of VTI have reported that VT insertion before the age of 6 months is beneficial 12,14 although VTI before palatoplasty increases the risk of prolonged otorrhea. 15,16 The present study found no significant association between cleft Schwarz et al 13 explained that in patients with a wide cleft, the surgeon must mobilize tissue more extensively and perform the adaption under a higher tissue drag. The drag on the eustachian tube may increase in patients with a wider cleft, enabling better middle ear ventilation.…”
Section: Cleft Palate Type and Ome Incidence And Durationcontrasting
confidence: 42%
See 2 more Smart Citations
“…Several studies on the timing of VTI have reported that VT insertion before the age of 6 months is beneficial 12,14 although VTI before palatoplasty increases the risk of prolonged otorrhea. 15,16 The present study found no significant association between cleft Schwarz et al 13 explained that in patients with a wide cleft, the surgeon must mobilize tissue more extensively and perform the adaption under a higher tissue drag. The drag on the eustachian tube may increase in patients with a wider cleft, enabling better middle ear ventilation.…”
Section: Cleft Palate Type and Ome Incidence And Durationcontrasting
confidence: 42%
“…The results of our study suggested that earlier VTI may be effective in patients with OME with a wide cleft who are often more prone to exacerbation and have a high incidence of severe AOM. Several studies on the timing of VTI have reported that VT insertion before the age of 6 months is beneficial 12,14 although VTI before palatoplasty increases the risk of prolonged otorrhea 15,16 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, uncertainty exists regarding whether VTI for OME benefits hearing or speech outcomes in patients with CLP (Zheng et al, 2003). Recent studies demonstrated a potential benefit in VTI prior to palatoplasty, yet the evidence is not widely accepted (Davis et al, 2020; Koempel et al, 2021). In contrast, recurrent OME or tube extrusion can occur frequently requiring repeat tympanostomies or long-term tube placement.…”
Section: Introductionmentioning
confidence: 99%